On the Regularity of Distribution for a Solution of SDE of a Jump Type with Arbitrary Levy Measure of the Noise - Kulik, A.M. (Український математичний журнал, 2005)
The local properties of distributions of solutions of SDE's with jumps are studied. Using the method based on the “time-wise” differentiation on the space of functionals of Poisson point measure, we give a full analog of Hormander condition, sufficient for the solution to have a regular distribution. This condition is formulated only in terms of coefficients of the equation and does not require any regularity properties of the Levy measure of the noise. Вивчаються локальні властивості розв'язків СДР зі стрибками. При застосуванні методу, який базується на „диференціюванні за часом" на просторі функціоналів від пуассонової точкової міри, наведено умову, яка аналогічна умові Хьормандера та достатня для того, щоб розв'язок мав регулярний розподіл. Ця умова формулюється тільки у термінах коефіцієнтів рівняння та не вимагає від міри Леві виконання будь-яких властивостей регулярності.